I'm not sure what you mean by "doubles up on subtraction." it looks like a math error to me. The equation

1 - Z = 1 + (-1) + (-1) + 1 + (-1) + 1...

is wrong. The correct derivation is

Given: Z = 1 - 1 + 1 - 1 + ...

1 - Z = 1 - (1 - 1 + 1 - 1 + ...)
1 - Z = 1 - 1 + 1 - 1 + 1 - ...
1 - Z = Z

You got all of the previous (finite) examples right, but they are irrelevant. The equation 1-Z=Z works only for the INFINITE series.

CAPTCHA
This question is for testing whether you are a human visitor and to prevent automated spam submissions.